La ciudadanía previsional como expresión de la ética del cuidado de sí - Castillo Ojeda, Shirley (2025)
This article proposes the concept of pension citizenship as an expression of the ethics of self-care, constituting a model that integrates individual autonomy with social commitment in the field of pension protection. To support this proposal, the ideas of classical philosophers such as Socrates, Plato, Aristotle, Epictetus, Marcus Aurelius and Epicurus are updated and articulated with the contemporary reflections of Foucault and Cortina. It is emphasized that pension citizenship emerges in dialogue with the dynamics of biopower and biopolitics present in modern pension policies, using the peruvian case as an example. Likewise, the importance of self-care and critical reflection on the power structures that shape pension systems is underscored. This study seeks to contribute to the critical reflection on achieving a dignified and secure old age through individual autonomy committed to the well-being of society.